Fusion bonded epoxy amine rebar powder coating
By using a combination of dihydrazide and toughening resin, combining bicatalyst and block copolymer, the shortcomings of the steel bar coating in low temperature flexibility and toughness are solved, and high flexibility, toughness and adhesion coating are achieved, avoiding the Crack and tear problems and improve processing consistency and curing speed.
Patent Information
- Application Number
- CN201980074452.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-14
- Filing Date
- 2019-11-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2039-11-26
AI Technical Summary
Existing reinforcement coatings have shortcomings in low temperature flexibility and toughness, resulting in cracks and tear problems, and the use of phenolic chemicals leads to poor delay and processing consistency.
Using dihydrazide as a curing agent, combined with high melting point epoxy resin and toughening resin, combined with dual catalyst encapsulation and block copolymers to form a highly flexible, tough and adhesion coating that allows no at low temperatures. The cracks bend and cure quickly.
实现了在-45℃下无裂纹弯曲,长期稳定性和快速固化,延迟性显著改善,避免了钢筋涂层的裂纹和撕裂问题,同时提高了加工一致性和粘附性。
Smart Images

Figure FDA0005078762730000011 
Figure GDA0005089125650000062 
Figure GDA0005089125650000072
Abstract
Description
Technical Field
[0001] This application claims the benefit of U.S. Provisional Application No. 62 / 779,767, filed on December 14, 2018, which is hereby incorporated by reference in its entirety.
[0002] The present invention relates generally to epoxy powder coating compositions and more particularly to a highly flexible and tough rebar surface coating that maintains demanding post-cure bending and fabrication. Background Art
[0003] Steel and concrete are the most widely used building materials in modern society. Fusion-bonded epoxy (FBE) coated rebar used in and with concrete is critical to extending the life of a variety of constructions, including infrastructure such as bridges, high-rise buildings, highways, etc. As actual application data over time has proven, rebar coated with FBE powder (power) has significantly improved corrosion resistance, similar to those of steel oil and gas pipeline applications. Recently, as many as two-thirds of bridges, highways, offshore civil and military buildings and ports, tunnels, wastewater treatment and chemical plants have adopted FBE coated rebar in construction. As of 2018, more than 10% of all rebar in the United States has been FBE coated, accounting for a total market value of more than $30 million for powder coated products.
[0004] Flexibility is critical for rebar coatings, but flexibility alone will seldom achieve crack-free performance. Most commercial FBE rebar coating products (not all) are poor in low temperature flexibility because they crack when bent post-cure (e.g., cracks or micro-tearing when bent 180° in 5 seconds at -45°C and / or in 0.7 seconds at ambient temperature). Coating film cracks tend to expose the rebar steel surface to moisture and oxygen, which promotes galvanic corrosion, leading to stress-induced swelling, and ultimately damage and collapse of building structures.
[0005] Rebar powder coating formulations are considered challenging due to having two CTQs (critical to quality requirements): 1) low temperature flexibility to allow rapid 180° bending without cracking at 8 to 12 mil dry film thickness, and 2) rapid cure to 15 to 20 seconds at the optional cure temperature to maintain coating line speeds at 50 ft / min to 70 ft / min without tracking marks on the first contact conveyor belt by the newly coated strip. To date, FBE rebar coatings have been formulated only with phenolic chemistries, utilizing phenolics with characteristics that favor fast response cure and good flow and leveling (due in part to the low melting point of phenolics at 75°C to 115°C), in addition to utilizing phenolic resin grades based on linear structures of bisphenol A to maximize flexibility or minimize modulus. Unfortunately, phenolic-based rebar formulations have poor retardance, especially when highly catalyzed to maximize ramp cure rates or shorten cure times, resulting in frequent and rapid deterioration of flexural properties. In addition, the intimate contact between the molecules of the phenolic resin and the molecules of the epoxy resin (melted and mixed together) after extrusion and during the entire life cycle leads to occasional processing and performance defects, and they are sometimes unavoidable. In summary, existing rebar powder coatings using phenols lack robustness in terms of delay and processing consistency, resulting in high rebar cracking and tearing and rework rates as widely seen. A lot of efforts made by some entities have been misguidedly focused on process modifications such as extrusion temperature control below 90°C to reduce premature curing, optional screw configurations (e.g., single screw and twin screw), dual or multiple extrusion, and particle size and distribution control. These attempts can help performance consistency to a certain extent, but they hardly affect the critical delays inherently associated with phenolic formulations. In addition, rebar cracking is fundamentally a function not only of flexibility, but also of toughness and adhesion. Flexibility alone cannot prevent microcracks; in order to solve the cracking problem in practice, sufficient toughness and adhesion required for tearing and / or peeling are sometimes overlooked.
[0006] The present invention solves all of the above problems in one solution by using FBE formulations of amine, especially dihydrazide curing chemistry, which is completely different from any phenol-centric modification. Dihydrazides (e.g., sebacic acid dihydrazide or SDH for short) (excluding adipic acid dihydrazide (ADH)) are primary (1°) amines with high melting points exceeding 187.0°C (phase transition temperature is much greater than that of phenols), thereby providing significantly improved epoxy resin delay compared to phenols. Therefore, the extrusion of epoxy resin / dihydrazide can be processed at normal temperatures of up to 125°C, instead of, for example, 90°C, which is often controlled for epoxy resin / phenols as explained; this significantly homogenizes the compounded premix, that is, evenly disperses but does not melt the highly latent dihydrazide particles with the molten resin system, provided that the dihydrazide particles are fine enough to be fully dispersed. In addition to using a main solid amine catalyst, such as imidazole of secondary (2°) and tertiary (3°) amines, dimethyl-amino-pyridine (DMAP) of only tertiary amine (3°), amine adducts of primary (1°) amines and secondary (2°) amines, or imidazole adducts of only tertiary amine (3°), a trace amount of a liquid-converted catalyst can be incorporated to improve adhesion between ingredients and bulk resin compatibility; according to the curing kinetics results, the additive catalyst also has high delay and reactivity. Such a main catalyst can be selected from a tertiary amine of the group consisting of: 2-methylimidazole, dimethylaminopyridine, or an amine adduct, or an imidazole adduct; and 2-propylimidazole can be selected as an additive catalyst.
[0007] Furthermore, the present invention includes a highly compatible toughening resin as part of a selected resin package optimized to enhance flexibility (or reduce modulus); the toughening agent can be a core-shell-rubber (CSR) modified 4-type epoxy resin in which MBS (methyl methacrylate-butadiene-styrene) is used as the core, or a block copolymer modified with epoxy-miscible and epoxy-immiscible segments in its structure. The latter (i.e., the derived block copolymer) is said to self-assemble to form a secondary toughening phase, thereby forming a bulk epoxy network during curing. As competitively tested within the scope of the present invention, CSR and block copolymer modified toughening resins outperformed other resins, such as CTBN or acrylic modified epoxy resins. In general, the innovative formulations represent an effective effort to address all rebar coating related problems in one solution. Summary of the invention
[0008] In one embodiment, the present invention provides a coated structural steel reinforcing bar and at least one FBE powder coating composition applied thereto. The powder coating composition of the present invention comprises:
[0009] (a) A flexible dihydrazide represented by the following general structure:
[0010] wherein n=4-20; and
[0011] (b) a dual catalyst package comprising a primary catalyst comprising at least one amine catalyst which can be selected from a tertiary amine of the group consisting of 2-methylimidazole, dimethylaminopyridine, or an amine adduct, or an imidazole adduct, and an additive catalyst which can be selected from an imidazole amine group, such as 2-propylimidazole (2PI); and
[0012] (c) an epoxy binder resin system, the epoxy binder resin system comprising:
[0013] a. 7.5 wt % to 22.5 wt % toughened resin;
[0014] b. 77.5 wt % to 92.5 wt % of a bulk epoxy encapsulant comprising a blend of epoxy resins having an EEW between 800 and 2000;
[0015] All weight % are based on the total weight of the resin, corresponding to an effectively stoichiometric resin to curing agent molar ratio of 1.0:1 to 5.0:1 (resin to curing agent).
[0016] Preferably, the toughening agent resin is a core-shell-rubber (CSR) modified epoxy resin (i.e., MBS or methyl methacrylate-butadiene-styrene copolymer as the core portion) having an EEW of 920 to 1090 g / eq and alternatively an amphiphilic OP (PEO-PEP) diblock copolymer modified epoxy resin having an EEW of 960 to 1060 g / eq and having epoxy miscible and epoxy immiscible portions structured as poly(ethylene oxide)-poly(ethylene propylene), wherein PEO is epoxy-philic. The bulk epoxy encapsulant may include, for example, a blend of type 4 resin and type 7 resin, or other combinations.
[0017] When applied to a steel bar test bar, as described herein, the coating of the present invention exhibits high flexibility at very low temperatures (-45° C.), and sufficient stability for up to 12 months without sacrificing final properties, and a very short cure time of as short as 16 seconds after preheating at 239° C. Preferably, according to the present invention, if the coating composition comprises a resin package of a combination of Type 4 and Type 7, the ratio of Type 4 resin to Type 7 resin is in the range of 1:8 to 4:1 or more preferably 1:6 to 2:1, wherein the Type 4 resin has an EEW between 800 and 1225, and the Type 7 resin has an EEW between 1650 and 2000.
[0018] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation mode of the present invention. The following description more specifically illustrates exemplary embodiments. In several places throughout the application, guidance is provided by lists of examples that can be used in various combinations. In each case, the cited lists are only used as representative groups and should not be interpreted as exclusive enumerations.
[0019] The details of one or more embodiments of the invention are set forth in the description below. Other features, objects, and advantages of the invention will be apparent from the description and from the claims.
[0020] Selected Definition
[0021] Unless otherwise indicated, the following terms as used herein have the meanings provided below.
[0022] When used in the context of a coating applied to a surface or substrate, the term "on" includes both coatings applied directly or indirectly to the surface or substrate. Thus, for example, a coating applied to a primer layer covering a substrate constitutes a coating applied to the substrate.
[0023] Unless otherwise indicated, the term "polymer" includes both homopolymers and copolymers (ie, polymers of two or more different monomers).
[0024] The terms "comprises" and variations thereof do not have a limiting meaning when they appear in the description and claims.
[0025] The terms "preferred" and "preferably" refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the statement of one or more preferred embodiments does not imply that other embodiments are unavailable, and is not intended to exclude other embodiments from the scope of the present invention. For example, the type 4 and type 7 resin combinations shown in the embodiments are not limited to this type or exclude any other; on the contrary, they include any resin mixtures of type 4, type 5, and type 7, such as individual types 4 or 5 or 7, type 4 and type 5, type 4 and type 7, type 5 and type 7, type 4 and type 5 and type 7, etc.
[0026] As used herein, "a", "an", "the", "at least one", and "one or more" are used interchangeably. Thus, for example, a coating composition comprising "an" additive can be interpreted to mean that the coating composition comprises "one or more" additives.
[0027] Also herein, numerical ranges recited by endpoints include all values contained within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.). In addition, disclosure of a range includes disclosure of all subranges included in the broader range (e.g., 1 to 5 discloses 1 to 4, 1.5 to 4.5, 1 to 2, etc.). DETAILED DESCRIPTION
[0028] The present invention solves the crack, microtear and peeling problems of steel bar coatings, along with improved processability and stability over time, wherein a selected flexible dihydrazide as a crosslinking agent is combined with a novel epoxy resin encapsulant consisting of a compatible toughening resin and a balanced bulk epoxy resin blend, such as Type 4 and Type 7 blends, providing flexibility (preventing cracks) and toughness (preventing microtears) as well as adhesion (preventing peeling). A dual catalyst encapsulant comprising 2PI (a viscous liquid or semi-solid at room temperature, encapsulated with fumed silica as a carrier at 60% active matter) provides compatibility and enhanced adhesion. At the same time, the present invention provides sufficient delay due to the dihydrazide amine having a melting temperature much higher than that of phenols, and also allows the use of favorable extrusion temperatures of up to 125°C (relatively high temperature extrusion enables fully homogenized compounding).
[0029] The combination of flexibility (via dihydrazide and resin blend) and adhesion (via flow and wetting as imparted in part by 2PI) and cohesion (via toughening) in the coating composition along with fully dispersed dihydrazide resin particles addresses the challenges of rebar coating.
[0030] The coatings of the present invention primarily utilize the chemical properties of dihydrazide to (1) achieve crack-free flexural properties at -45°C; 2) improve product retardation (DSC onset temperature >130°C, while existing phenolic formulations ≤120°C, running at 20°C / min), which results in adequate shelf life for storage and transportation with little concern for premature curing or loss of final properties over time. In addition, they allow regular and user-friendly extrusion temperature settings up to 125°C (no longer limited to ≤90°C sometimes used on phenolic cured rebar products).
[0031] The coating of the present invention utilizes a flexible dihydrazide together with an epoxy encapsulator with maximized flexibility and flow potential, which allows the coating to withstand cracking when bent at various degrees / diameter (° / PD) at very low temperatures (down to -45°C) while maintaining strong adhesion to the steel rebar substrate. Epoxy thermoset curing is a complex process involving a series of competing reactions consisting of etherification (epoxy homopolymerization) and cross-linking polyaddition reactions initiated or catalyzed by tertiary (3°) amines. Homopolymerization represents linear chain growth, which ultimately provides flexibility to support crack-free bending, while cross-linking results in a polymer network with sufficient toughness, mechanical strength and integrity.
[0032] Dihydrazide
[0033] The curing agent or crosslinking agent used in the present invention includes one or more flexible dihydrazides having four (4) active primary (1°) amine functional groups having the following general structure:
[0034] Where n = 4-20;
[0035] The ratio of epoxy resin equivalent weight (EEW) to amine hydrogen equivalent weight (EW-NH) in the present invention should be selected within the range of 1.0: 1 to 6.0: 1, preferably between 1.2: 1 and 3.0: 1. For example, for epoxy resins having reactive glycidyl groups, the more preferred molar ratio of glycidyl groups in the epoxy resin to amino groups in the curing agent is in the range of 1.5: 1 to 2.8: 1.
[0036] In one embodiment, dihydrazides such as ADH, SDH, DDH, LDH and UDH are identified as suitable curing agents in the present invention, wherein SDH (melting temperature T m =187℃, while the T of phenols m <115°C) is preferred. SDH has eight (8) CH2 straight chains between the terminal functional groups, imparting flexibility. SDH has a high melting point that provides the desired delay. Preferred dihydrazides include the following:
[0037]
[0038] H2N-NH-CO-(CH2) 18 -CO-NH-NH2
[0039] c)DDH (Decanedihydrazide) d)LDH (Icosanedioic acid dihydrazide)
[0040] EW-NH: 64.5, T m =190℃EW-NH:92.5,T m =175℃
[0041] In one embodiment, the hydrazide may contain unsaturation between the carbonyl moieties, such as in:
[0042]
[0043] e)UDH (eicosadioic acid dihydrazide)
[0044] EW-NH: 91.5, melting point 160℃
[0045] The SDH as the core crosslinker composition for use in the present invention preferably has a fine particle size of 3 to 6 microns on average. The fine particle size and narrow particle size distribution allow the unmelted SDH resin particles to be fully and evenly dispersed into the resin system through the extruder, ultimately facilitating acceptable and best possible performance in terms of flex cracking. By comparison, the coarse particle size of SDH was determined to be 30 to 60 microns on average to consistently destroy the steel bar cracking performance.
[0046] catalyst
[0047] The catalyst used in the present invention is a dual catalyst system. The primary catalyst that can be used in the present invention is an amine catalyst, preferably 2-methylimidazole (2MI), or DMAP, or an amine adduct, or an imidazole adduct, as shown in the structure below. 2MI and DMAP and imidazole adducts (shown) are equivalent in reactivity at a given phr (per hundred resin) loading according to DSC curing kinetic data. Amine adducts (such as, for example, Epikure P100, Aradur 3088 or Epikure P101) are slightly less reactive, but their reactivity can be increased by increasing the loading. Compared with 2MI, DMAP and imidazole adducts (containing only 3° amine) tend to promote more epoxy homopolymerization during crosslinking; as taught by the present invention, homopolymerization imparts flexibility. Preferably, the amount of 2MI or DMAP or amine adduct or imidazole adduct in these inventive compositions is generally in the range of 1 phr to 4 phr in one embodiment; more preferably 1 phr to 2 phr, in another embodiment closely related to the stoichiometric ratio to be selected and depending on the gel and cure time to be achieved.
[0048]
[0049] MW:110.2,T m 62℃MW:82.1,T m 145℃MW:122.2,T m 113℃
[0050] d) Amine adducts: MW is different, T m 85℃-105℃
[0051]
[0052] e) Imidazole adducts: different MW, T m 85℃-105℃
[0053]
[0054] The second additive catalyst according to the present invention is also from the imidazole amine group, more specifically, 2PI, which is the only viscous liquid or semi-solid imidazole at ambient temperature. Due to its liquid form, 2PI has better compatibility or dispersibility with epoxy resins than 2MI or DMAP or amine / imidazole adducts, which facilitates the homogenized mixing of the coating ingredients in the present invention and promotes flow and leveling, thereby improving adhesion to support crack-free or peel-off bending performance in combination with the main catalyst even at low phr loading levels. At the same time, 2PI has a much higher delay than 2MI or DMAP or amine / imidazole adducts (due to steric effects), while it becomes highly reactive when thermally activated (as reactive as amine adducts, but not as reactive as 2MI or DMAP or imidazole adducts), thereby improving coating stability while maintaining the reactivity required for rapid curing. The amount of 2PI can also be selected by the curing kinetics results. For example, the amount of 100% active matter of 2PI may range from 1 to 10 wt % of the amount of procatalyst such as 2MI or DMAP or amine / imidazole adduct used in one embodiment of the present invention.
[0055] Toughened resin
[0056] The use of toughened epoxy resins in the resin compositions of the present invention generally results in enhanced cohesion (supports no flex tearing) without compromising flexibility (supports no flex cracking), provided that the toughened resin is highly compatible with the bulk resin.
[0057] Toughening agents are typically organic polymer additives that achieve phase separation in the cured epoxy resin network. Toughening resins useful in the present invention may include, for example, MBS or methyl methacrylate-butadiene-styrene copolymer-modified core-shell rubber (CSR) type 4 epoxy resins, block copolymer-modified, polyol-modified, DCPD (dicyclopentadiene)-modified, rubber (CTBN, acrylic, etc.)-modified, or mixtures thereof.
[0058] One embodiment of the toughened epoxy resin useful in the present invention may include, for example, a CSR modified epoxy resin, such as Fortegra 304 useful in the present invention, and alternatively an amphiphilic diblock copolymer modified epoxy resin. Test polyol and DCPD modified (such as XU-19741 and Epiclon HP-7200H or XD-1000, respectively) are slightly worse in micro-tear. Preferably, the amphiphilic diblock copolymer modified epoxy resin useful in the present invention may include a PEO-PEP (polyethylene-polyethylene-propylene) modified epoxy resin derived from bisphenol A; more preferably, the toughening agent used in the present invention is FORTEGRA TM664-12. Both Fortegra 304 and 664-12 proved to be highly compatible with the compositions of the present invention, and they could self-assemble to form a second phase that toughened the rubber core during cure.
[0059] The concentration of the toughening agent used in the curable composition described herein can depend on a variety of factors, including the equivalent weight of the polymer, and the desired flexibility and toughening characteristics of the product made from the curable composition. Generally speaking, the toughening agent can be used in an amount sufficient to provide enough toughness to the resulting composite material to prevent microcracks (i.e., tearing) of the coating. For example, based on the gross weight of the resin composition, the amount of the toughened resin can generally be in the range of about 7.5 wt % to about 22.5 wt % in one embodiment, in the range of about 10 wt % to about 20 wt % in another embodiment, and in the range of about 12 wt % to about 15 wt % in another embodiment.
[0060] Epoxy resin
[0061] The bulk epoxy resin package as one of the possible options preferably consists of 70% Type 7 (e.g., Epon 1007F), 17.5% Type 4 (e.g., Epon 2004), and 12.5% toughening resin (e.g., Fortegra 664-12 or Fortegra 304), once cured preferably by dihydrazide with ADH and SDH used in an equivalent ratio (crosslinker to resin) of 1:1.5 to 1:2.8, and preferably catalyzed by a dual catalyst package of 1.25 to 1.80 phr of 2MI as described above and 2PI totaling about 3.0 wt% of 2MI, yields the desired system of excellent flexibility and adhesion and toughness. It should be noted that the amount of catalyst was selected based on the cure kinetics results; 2PI was identified as improving or supplementing the properties therein.
[0062]
[0063]
[0064] Various combinations of epoxy resins may be used if desired, but the combinations disclosed in the present invention appear to perform best. The solid epoxy resins may have an equivalent epoxy weight (EEW) of 800 to 2000. These resins are often described by their "type" to indicate the molecular weight (MW). Types 4 and 7 are suitable for use here; again, this does not mean that the resin encapsulation in the composition of the present invention is limited to only this particular option.
[0065] Type 4 resins may have an EEW of 800 to 1225, type 5 resins may have an EEW of 1300 to 1350, and type 7 resins may have an EEW of 1650 to 2000. Commercial examples of type 4 resins include Epon-2004, KD-214C, YD-904. Commercial examples of type 5 resins include EPON 2005, YD-905, and commercial examples of type 7 resins include Epon-1007 F, YD-017.
[0066] In a preferred embodiment, the powder coating composition comprises an epoxy resin system comprising:
[0067] (a) 7.5 wt % to 22.5 wt % of a toughening agent resin, wherein the toughening agent resin is Fortegra
[0068] 304 or 664-12;
[0069] (b) 7.5 wt % to 62.5 wt % of a Type 4 epoxy resin having an EEW between 800 and 1225; and
[0070] (c) 15.0 wt % to 85.0 wt % of a Type 7 epoxy resin having an EEW between 1650 and 2000, all wt % being based on the total weight of the resin.
[0071] According to the present invention, in the case of using the type 4 resin and the type 7 resin, the ratio of the type 4 resin to the type 7 resin is in the range of 1:8 to 4:1.
[0072] Thus, in a preferred embodiment, the powder composition described herein is a fusion bonded epoxy (FBE) composition. The preferred composition comprises an epoxy resin prepared from a homogeneous mixture of a toughening resin, a Type 4 epoxy resin, and a Type 7 epoxy resin, together with a flexible dihydrazide curing agent and a bisimidazole catalyst. In one aspect, the fusion bonded epoxy composition is present in an amount of about 65 wt % to 95 wt %, preferably about 70 wt % to 95 wt %, more preferably about 77.5 wt % to 92.5 wt %, and most preferably about 80 wt % to 92.5 wt %, based on the total weight of the powder composition.
[0073] In one embodiment, the polymer binder is dry mixed with any additives, functionalized pigments, fillers, etc., and then melt blended, typically by passing through an extruder. The resulting extrudate is solidified by cooling and then ground or pulverized to form a powder. Alternatively, the additives described herein can be combined with other compositions to be added to the powder composition as a post-addition after extrusion.
[0074] As described above, additives may be added prior to extrusion and as part of the extruded powder composition, or may be added after extrusion. Suitable additives for post-extrusion addition include materials that would not function well if they were added prior to extrusion.
[0075] Optional additives may include materials that provide a desired effect on the powder finish or powder composition, or additives that can improve the application, melting and / or curing of the powder, or the final properties or appearance. Examples of useful optional additives include: pigments and fillers, others are curing catalysts, antioxidants, color stabilizers, anti-corrosion additives, degassing additives, flow control agents, etc.
[0076] Example
[0077] These examples are for illustrative purposes only and are not intended to limit the scope of the appended claims. Unless otherwise specified, all parts, percentages, ratios, etc. in the examples and description are by weight.
[0078] The exemplary coating compositions of the present invention may contain additional materials in different concentrations that may be required according to individual needs. For example, the composition may also contain one or more fillers for controlling the wire drawing mesh, pigments, fillers, adhesion promoters, and combinations thereof.
[0079] If desired, the coating composition of the present invention may include at least 0.1 wt% pigment based on the total weight of dry epoxy resin. Typically, if used, the coating composition of the present invention includes no more than 5.0 wt% pigment based on the total weight of solid resin.
[0080] When ready to apply, the various parts of the coating composition are mixed together just before spraying. The coating composition can be applied directly to preheated steel and immediately cured by residual heat. The flexibility properties of the cured coating composition can be measured according to the bend test provided.
[0081] Example
[0082] Each batch of about 1500 grams of premix was mixed for 35 seconds by a high shear propeller mixer (full mixing should also be ensured during production). The mixture was extruded using a guarded twin screw at 85°C (Z3) and 123°C (Zone 4) at 500 rpm with a feed rate of 18-20. The flakes were ground by a Bantam grinder and then sieved through a 94T size screen.
[0083]
[0084]
[0085] The powder was sprayed onto rebar and dowel rods preheated at 232°C or 239°C for 30 seconds, 25 seconds and 20 seconds (35 seconds and 30 seconds if 232°C preheat) or other specified design cure time. The coated rebar and dowel rods 8-12 mils, bent at -45°C, no cracking or peeling, minimal tearing of Example B and normal amount of wire drawing mesh lasted for up to 12 months in addition to a glossy finish without yellowing or discoloration. It should be noted that the existing product is a commercial product with a coating composition based on conventional phenolic curing chemistry, and its T g The amine formulation of the present invention has a lower T at 101°C to 103.0°C. g A lower Tg is typically advantageous in terms of flexibility, since the latter is somewhat inversely proportional to the former.
[0086] Test Method: Flexibility tests were performed with a Tecmor SEIM type mechanical bender at -45°C for 2 hours post cure and 24 hours post cure. For all, preheat at 239°C for 45 minutes.
[0087]
[0088] Note: ACR (actual crack rate) ≤ 0.19 is considered qualified
[0089] Example C of Formulation, Preparation and Testing:
[0090]
[0091] The cure kinetics determined by DSC for Example C (i.e., the upgraded SDH formulation) are listed in the table above, which predicts cure times of 17.3 seconds and 14.9 seconds at 232°C and 239°C, respectively, which is consistent with and confirmed by the rebar bending results.
Claims
1. A powder coating composition, comprising: (a) A flexible dihydrazide amine having an average particle size of less than 10 microns, which is represented by the following general structure: wherein n=8-20; and (b) a dual catalyst package comprising 1 to 4 phr of a primary catalyst and an additive catalyst, wherein the primary catalyst is selected from 2-methylimidazole 2MI, dimethylaminopyridine, an amine adduct or an imidazole adduct; and the additive catalyst is selected from imidazole amine, present in an amount of 1 to 10 wt % based on the total weight of the primary catalyst; and (c) an epoxy binder resin system, the epoxy binder resin system comprising: a. 10 to 20 wt % toughening resin; and b. 80 wt % to 90 wt % of a bulk epoxy encapsulant comprising a blend of epoxy resins having an EEW between 800 and 2000; All weight % are based on the total weight of the resin, corresponding to a stoichiometric molar ratio of resin to crosslinker of 1.2:1 to 3.0:
1.
2. The powder coating composition according to claim 1, wherein the blend of epoxy resins is a blend of a type 4 resin having an EEW between 800 and 1225 and a type 7 resin having an EEW between 1650 and 2000.
3. The powder coating composition according to claim 2, wherein the ratio of the type 4 resin to the type 7 resin is in the range of 1:8 to 4:
1.
4. The powder coating composition according to claim 2, wherein the ratio of the type 4 resin to the type 7 resin is in the range of 1:6 to 2:
1.
5. The powder coating composition according to claim 1, wherein the toughened resin is a core-shell-rubber modified with a MBS copolymer core and a Type 4 epoxy resin shell or an amphiphilic PEO-PEP diblock copolymer modified Type 4 epoxy resin, both of which have high compatibility with the bulk resin and the Type 4 resin of the EEW.
6. The powder coating composition according to claim 1, wherein the additive catalyst is 2-propylimidazole 2PI.
7. A coated structural steel rebar, wherein the coated rebar has applied thereto a coating composition comprising the powder coating composition according to any one of claims 1 to 6.
8. The coated structural steel rebar according to claim 7, wherein the powder coating composition cures within 16-28 seconds after preheating at 239°C.
9. The coated structural steel rebar of claim 7, wherein when the coating composition is cured, the coating exhibits no cracking or tearing when the rebar is bent at -45°C after being held at -45°C for up to 24 hours.
